2017
DOI: 10.9734/arrb/2017/35990
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Artemisia judaica against Doxorubicin-Induced Toxicity in Mice

Abstract: Aim: The present study aimed to investigate the protective effect of Artemisia Judaica (A. Judaica) against doxorubicin (DOX)-induced toxicity in male mice. Place and Duration of Study: Department of Cell Biology, Genetic engineering and biotechnology division, National research centre, Egypt, between March 2016 and February 2017. Methodology: Male mice were divided into 7 groups (n=10) and treated as follow: the control group, the group treated with DMSO, the group injected (i.p.) with DOX , the groups treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Moreover, the cytotoxic activity of the alcoholic crude extract was previously reported against hepatocellular carcinoma (HepG2), breast cancer (MCF-7), and colon tumor (LoVo) cell lines. This was explained through its ability to inhibit cell proliferation, angiogenesis, and inflammation in addition to its a beneficial protective effect against doxorubicin-induced toxicity in mice [ 15 , 16 , 17 , 18 , 19 ]. Both the ethyl acetate and petroleum ether fractions exhibited remarkable renal protective activity in hyperlipidemic and hyperglycemic rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cytotoxic activity of the alcoholic crude extract was previously reported against hepatocellular carcinoma (HepG2), breast cancer (MCF-7), and colon tumor (LoVo) cell lines. This was explained through its ability to inhibit cell proliferation, angiogenesis, and inflammation in addition to its a beneficial protective effect against doxorubicin-induced toxicity in mice [ 15 , 16 , 17 , 18 , 19 ]. Both the ethyl acetate and petroleum ether fractions exhibited remarkable renal protective activity in hyperlipidemic and hyperglycemic rats [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…E. spinosus is a perennial spiny herb; its preparations were used in traditional medicine as an abortifacient, anti-diabetic and diuretic and to improve blood circulation [35]. A. judaica is a perennial aromatic shrub commonly used as an anti-helminthic and reported to have anti-microbial, anti-inflammatory, anti-oxidant [36] and anti-diabetic effects [37]. No previous studies have investigated the anti-protozoal potential of these herbs on Blastocystis spp.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with previous reports which showed that A. Judaica protected against organs damage and cellular enzymes leakage in rodents through its membrane-stabilizing property . 8,19,39 The protective effect of A. judaica against diabetes-mediated cardiac injury was further confirmed by the histological findings. H&E stained sections in the heart of both control ( Figure 3A) and A. judaicaadministrated rats ( Figure 3B) showed normal morphological features microscopically.…”
Section: A Judaica Protects Against Hyperglycaemia-induced Cardiac Imentioning
confidence: 79%
“…Remarkably, A. judaica treatment attenuated MDA and boosted antioxidants in the hearts of diabetic rats. In this context, A. judaica attenuated hyperglycaemia 8,35 and doxorubicin 19 induced tissue injury by suppressing lipid peroxidation and restoration of endogenous antioxidants. 17 These findings indicate that A. judaica could protect against cardiac injury by attenuating oxidative stress, which could be attributed to its antioxidant and antiperoxidative properties.…”
Section: A Judaica Attenuates Myocardial Oxidative Stress In Diabetimentioning
confidence: 99%
See 1 more Smart Citation